Land Equivalent Ratio of Cowpea–Sorghum Relay Intercrop as Affected by Different Cattle Manure Application Rates Under Smallholder Farming System - Parwada, Cosmas; Chinyama, Trust Antony (Frontiers in Sustainable Food Systems, 2021)
Poor soil fertility is a major challenge in crop production in the communal farming areas of Zimbabwe. Intercropping legumes and cereals is a common soil fertility management technology among the farmers. A 3-year field experiment was conducted to evaluate intercropping advantages in cowpea-sorghum in response to different cattle manure application rates. A 3 × 4 factorial laid in a completely randomized block design (CRBD) with 3 replicates. The treatments were three cropping systems (sorghum sole, cowpea sole and cowpea-sorghum intercrop) and four cattle manure application rates (0%, 50%, 75% and 100%). Crop growth rate (CGR), grain yield, harvest index (HI), relative competitive ability of each crop and the land equivalent ratio (LER) were measured. Analysis of variance and non-linear regression analyses were done to determine the yield benefits of cowpea-sorghum intercrop and estimate the relative competitive ability respectively. Application of >75% cattle manure in a cowpea-sorghum intercrop enhanced the sorghum grain yield and HI more than in cowpea. Cowpeas had higher CRG at >75% cattle manure application rates on both intercrop and sole cropping than sorghum but with lower grain yield. Intra-specific competitive stress in sorghum was reduced at a high (>75%) quantity of manure applied. Effects of the intra-specific competition in cowpea were stronger on grain yield than biomass at >75% manure application rates. The LER was >1 in all the treatments and was highest (2.73) on average of the study period under the cowpea-sorghum intercrop without cattle manure. High quantities (75% application rates) of cattle manure in a cowpea-sorghum intercrop enhanced grain yield in sorghum and vegetative growth in cowpeas. It is therefore recommended to use >75% cattle manure application rate in the intercrop if one wants higher grain in sorghum and high biomass in cowpeas possibly for fodder. Further studies are recommended to quantify the rate of increase in available N under the cowpea-sorghum intercrop with >75% cattle manure application rates.